The Use of Media for Increasing the Vocabulary of EFL Learners - Alfred Snae (Widya Accarya, 2023)
Using media in teaching foreign language especially English vocabulary for junior high school students obviously help them improve their learning achievement. This study is focused on the use of various media in improving students’ vocabulary. It is an experimental study done to the second-grade students of a junior high school in Kupang, Indonesia. The quantitative method of analysis is used in presenting the data. Based on the calculation using the t-test formula, it is found that the use of various media in teaching English vocabulary improved the students’ learning achievement. It is proved by the result of the t-test on the treatment group’s pre-test and control group. The result of the pre-test was 1.152 lower than the result of the t-test of the treatment group’s post-test and the control group’s post-test was 4.84. Based on the data found that has been analyzed, it may be concluded that teaching English using various media improved students’ learning achievement since the result of the t-test is 4.84 which is higher than the value of the t-table, 2.048. More experimental studies need to be conducted to provide more information about the use of the media because students’ background of language competencies is suspected to take effect during the treatment.